Two Trichome Birefringence-Like Proteins Mediate Xylan Acetylation, Which Is Essential for Leaf Blight Resistance in Rice. Issue 1 (18th November 2016) - Gao, Yaping; He, Congwu; Zhang, Dongmei; Liu, Xiangling; Xu, Zuopeng; Tian, Yanbao; Liu, Xue-Hui; Zang, Shanshan; Pauly, Markus; Zhou, Yihua; Zhang, Baocai
Abstract : OsTBL1 and OsTBL2 represent xylan acetyltransferases, which catalyze addition of acetyl groups onto the 2-O and 3-O position of xylosyl residues and is essential for pathogen resistance in rice. Abstract: Acetylation is a ubiquitous modification on cell wall polymers, which play a structural role in plant growth and stress defenses. However, the mechanisms for how crop plants accomplish cell wall polymer O -acetylation are largely unknown. Here, we report on the isolation and characterization of two trichome birefringence-like ( tbl ) mutants in rice ( Oryza sativa ), which are affected in xylan O -acetylation. ostbl1 and ostbl2 single mutant and the tbl1 tbl2 double mutant displayed a stunted growth phenotype with varied degree of dwarfism. As shown by chemical assays, the wall acetylation level is affected in the mutants and the knock-down and overexpression transgenic plants. Furthermore, NMR spectroscopy analyses showed that all those mutants have varied decreases in xylan monoacetylation. The divergent expression levels of OsTBL1 and OsTBL2 explained the chemotype difference and indicated that OsTBL1 is a functionally dominant gene. OsTBL1 was found to be Golgi-localized. The recombinant OsTBL1 protein incorporates acetyl groups onto xylan. By using xylopentaose, a preferred acceptor substrate, OsTBL1 can transfer up to four acetyl residues onto xylopentaose, and this activity showed saturable kinetics. 2D-NMR spectroscopy showed that OsTBL1 transfers acetate to both 2- O and 3- O sites of xylosyl residues. In addition, ostbl1 and tbl1 tbl2 displayed susceptibility to rice blight disease, indicating that this xylan modification is required for pathogen resistance. This study identifies the major genes responsible for xylan acetylation in rice plants.